Distribution of Pine Woolly Adelgids Infestation on Pinus merkusii Plantation in Java - Rachmatsyah, Oemijati; Siregar, Ulfah Juniarti; Haneda, Noor Farikhah; Nandika, Dodi; Hidayat, Purnama (Jurnal Manajemen Hutan Tropika, 2012)
Pine woolly adelgid is a recently found exotic pest attacking seedling up to grown plants of Pinus merkusii plantations forest. Since its discovery, there were not much information about it. The objectives of this research were to study pine woolly adelgids distribution, symptoms and indicators, and its scale of infestations on Pinus merkusii plantation in Java, to determine the presence of any specific P. merkusii sites invaded by pine woolly adelgids, considering the pests were native to boreal and temperate areas. Hypothesis was pine woolly adelgids infestation on P. merkusii in Java is consistent with their native distribution. There were 9 Forest Management Unit (KPH) with infested P. merkusii plantations which were located at altitude between 900 to 1,700 m asl. with temperature ranging 16-22 °C and air humidity 80-90%. This indicated that Pine Woolly Adelgids required low temperature to survive, which was consistent with their original distribution. Host preference with regard to scale of infestation was closely related to temperature, altitude, and number of trees per hectare. The scale of infestation varied among regions, from light to heavy infested/death of trees.